Calcium biomineralizations associated to bioclastic deposits in coastal pedostratigraphic sequences of the Southeastern Pampean Plain, Argentina - Osterrieth, Margarita (2017)
The biomineralization process is genetically controlled, and it is theresult of the metabolic activity of different organisms. Microorganisms, plants andanimals produce calcium biomineralizations, calcium oxalates and carbonates beingthe most representative. The Quaternary pedosedimentary sequences of the south-eastern coast of Buenos Aires province evolved from bioclastic and loess sediments, reworked by water and/or wind action. Calcium biomineralizations play animportant role in the development of soils and contribute to differentiate sedimentary levels affected by pedogenesis. This work aims to characterize calciumbiomineralizations in bioclastic, loessic and fluvio-eolian pedosedimentarysequences, typical of coastal environments of the southeastern Buenos Aires province. Modal soil profiles were defined in pedosedimentary sequences of the fluvio-eolian and coastal plains, in which disturbed and undisturbed samples wereanalyzed. Samples were analyzed at different scales of resolution: mesoscopic,microscopic and submicroscopic, using optical microscopy and scanning electronmicroscopy/energy-dispersive X-ray spectroscopy (SEM/EDX). Organic matter23 content, pH, particle size distribution, mineralogy and calcium content were alsoquantified. Three geopedological units were differentiated in a sequence developedon loess mantle deposits: dunes and interdunes, coastal lagoon/paleo-coastal lagoonand shell ridges. In soils with incipient development, calcium biomineralizations arescarce, mainly associated with isolated bioclasts. In soils with more pedologicaldevelopment, bioclasts are affected by bioerosion through microorganism action(fungi and algae), and subsequently calcium re-precipitated as secondary oxalatesand carbonates (biomineralization). These Biomineralizations also weakly add orbind skeletal components, incorporating themselves into the matrix of soils andsediments. The type and diversity of calcium biomineralizations increase directly inrelation with time and pedogenetic evolution; so, these biomineralizations havebeen determinant in the origin, evolution and resistance to natural and anthropicdegradation of the late Quaternary pedosedimentary sequences of southeasternBuenos Aires province, Argentina.